Analisis Pola Komunikasi dalam Disfungsional Family & Resiliensi pada Anak Kota Tegal - Rizky, Alisya Ainnur; Suparto, Diryo; Florina, Ike Desi (Jurnal Studi Ilmu Sosial dan Politik, 2025)
Purpose: This study aimed to analyze communication patterns in dysfunctional families and understand how resilience develops in children in Tegal City. Methodology: This study used a qualitative approach with a case study method. Data were collected through in-depth interviews with children from dysfunctional families and interviews with parents, teachers, and child psychologists in Tegal City. Results: Communication patterns in dysfunctional families in Tegal City significantly impact children’s emotional and social development. However, resilience is a key factor that allows children to survive and thrive under difficult conditions. Support from the surrounding environment, such as schools and social communities, plays an important role in helping children from dysfunctional families build psychological resilience and achieve a better life. Conclusions: This study shows that communication patterns in dysfunctional families in Tegal Citsy, both in structurally intact and incomplete families, significantly influence children's resilience levels. Limitations: Research on the analysis of communication patterns in dysfunctional families and resilience in children in Tegal City has several limitations, namely having a limited sample, using qualitative methods and focusing on one location (Tegal City). Contribution: This study can improve understanding and increase public awareness of communication patterns in dysfunctional families and child resilience. This study can also be used by clinical practitioners to develop more effective intervention strategies in the future.